ANALYSIS OF PRODUCING MILK AND DEVELOP PERSPECTIVE OF IN THE REPUBLIC OF SERBIA - Nataša Kljajić; Slavica Arsić; Mirjana Savić (Ekonomika Poljoprivrede (1979), 2009)
Research in this paper work tends to show basic characteristic in producing cow and sheep milk in the Republic of Serbia in period 1998 – 2007. Paper work analyzed production cow and sheep milk in regions in Central Serbia and Vojvodina, also paper analyzed changes which held in production during researching period and participation of production cow and sheep milk in the Republic of Serbia, using base index.